Social construction of the coastal erosion and contours of natural resource management in Mozambique - Amaral, Giverage Alves do (Faculdade de Ciências e Letras - Unesp - Araraquara., 2014)
This article is a reflection through which we intend to understand the contours of natural resource management in Mozambique, having as object of analysis the erosion Coastal of Costa do Sol beach. The Mozambican coast is characterized by a great diversity of habitats and has a great natural wealth, but on the other hand, this coastal ecosystem is a very weak, and this is one of the most glaring environmental problems of today in Mozambique, and undoubtedly is a reflection of the socio-environmental context of conflicts which itself sets a great challenge to the implementation of environmental policy in Mozambique, whose law determines the use and management of environmental components in order to promote the improvement of the quality of life of citizens.